IMPLANT SURVIVAL RATE UNDER IMMEDIATE LOADING IN FULL-ARCH RECONSTRUCTION: A NARRATIVE REVIEW - SANTOSO, HALUANRY DOANE; KAMAL, IDSON; MASULILI, SRI LELYATI C.; WIDARYONO, ADITYO; AYUNINGTYAS, DEWI; HARTONO, VALDY (International Journal of Applied Pharmaceutics, 2025)
Immediate implant loading in full-arch rehabilitation has become prominent due to fewer visits than delayed implant loading and increased success reports. This study evaluates and compares the implant survival rate in full-arch reconstruction under immediate loading with delayed loading protocol. This review was conducted using online databases, including ResearchGate, PubMed, and MDPI database, combining the following terms: “Dental implants,” “Immediate loading,” “Delayed loading,” and “Fixed Full-arch reconstruction.” The inclusion criteria and search strategy were limited to human studies published in English. The selected articles were clinical studies or retrospective studies published between 2019 and 2024. Immediate Loading (IL) vs Delayed Loading (DL): IL of implants in full-arch reconstructions has shown high survival rates comparable to DL. Studies report survival rates of 99.7% for IL and 97.2% for DL after five years of follow-up. IL has demonstrated excellent clinical outcomes, with minimal bone loss and high prosthesis survival rates. Immediate restoration protocols, such as the flat one-bridge technique, have also shown a 99.6% implant survival rate over a median follow-up of 86 mo. Immediate implant loading in full-arch reconstruction exhibited a high survival rate and predictable clinical outcomes, making them a viable option for the rehabilitation of edentulous patients. This protocol reduced the treatment time and enhanced patient satisfaction, thus offering a reliable alternative to the delayed loading method.